GLOBAL DECREASES IN TOTAL OZONE DURING THE WINTER MONTHS - タカオ, トシノリ; TAKAO, Toshinori (National Institute of Polar Research, 1990)
P(論文) Global network of total ozone measurements by Dobson spectrophotometer shows ozone decrease in recent years. At midlatitudes of the Northern Hemisphere, ozone loss was significant during the winter months of 1983 and 1985. In some regions, there is a positive correlation between the annual mean of total ozone amounts and the solar cycle. departmental bulletin paper